The shape of the wealth distribution and differences in wealth inequality across Euro area countries - Martin Biewen; Stefan Glaisner; Rolf Kleimann (The Journal of Economic Inequality, 2024)
Based on data from the Eurosystem Household Finance and Consumption Survey (HFCS), we revisit the question of how differences in household characteristics can account for cross-country differences in wealth inequality. We first show that commonly used RIF-decompositions are typically tested positive for specification error due to the large differences in household characteristics between countries. We then present an alternative analysis for which we introduce a convenient graphical representation of the wealth distribution. Our results show that not only differences in wealth inequality but also differences in distributional shape can be largely accounted for by differences in homeownership across countries, but that, for some country comparisons, differences in household incomes also matter.
Keywords: 300; RIF-decomposition; Reweighting; Transformation; Homeownership